Analisis Faktor Penyebab Kesulitan Membaca Permulaan Pada Siswa Kelas I SDN Argopeni Tahun Ajaran 2019/2020 - Erna Masroah; Wahyudi Wahyudi; Rokhmaniyah Rokhmaniyah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The study aimed to determine the early reading difficulties to first grade students of SDN Argopeni in academic year of 2019/2020, to determine the causal factors of early reading difficulties, and to describe the solutions to overcome early reading difficulties to first grade students of SDN Argopeni in academic year of 2019/2020. It was qualitative research. The subjects were four students of first grade. The results showed that: (1) the early reading difficulties of first grade students were: (a) not able to analyze words into letters, (b) not able to understand letter-sound, (c) not able to arrange words and letters and read word for word; (2) the causal factors of early reading difficulties were: (a) internal factors, (b) external factors; (3) alternative solutions applied by the teachers to overcome the early reading difficulties were: (a) having additional classes, (b) applying interesting media, (c) using the SAS method. It concludes that there are difficulties of early reading, the causal factors, and the teachers have applied the solution to overcome the early reading difficulties.